2019
DOI: 10.1590/1516-3180.2018.0264090119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changes to the formal curriculum on medical students’ motivation towards learning: a prospective cohort study

Abstract: INTRODUCTIONLearning is influenced by different factors, and learners' engagement is primordial among these factors. In turn, engagement is affected by students' motivation and their perception of the relevance of the aims and features of the learning process. 1 Consequently, well-motivated students seem to have more favorable study behavior and higher quality of learning. 1,2 According to the self-determination proposition, 2 motivation can be understood as a propensity to move or to do something. Motivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Del-Ben et al (2019) found that students with the reformed curriculum (small group discussions, clinical activities with real patients, promoting active learning methods) had higher autonomous and controlled motivation than those of the traditional (science based, mainly lectures) curriculum. 17 Clearly teaching methods can improve or weaken motivation levels. For example, the introduction of standardization in medical education, problem-based and learner-centered methodologies improved students’ cognitive and metacognitive processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Del-Ben et al (2019) found that students with the reformed curriculum (small group discussions, clinical activities with real patients, promoting active learning methods) had higher autonomous and controlled motivation than those of the traditional (science based, mainly lectures) curriculum. 17 Clearly teaching methods can improve or weaken motivation levels. For example, the introduction of standardization in medical education, problem-based and learner-centered methodologies improved students’ cognitive and metacognitive processing.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Although education environment like educational contexts and teachers' autonomy-support influence motivation levels, studies to compare students' motivation in association with their curriculum type are rare and motivational processes are substantially undervalued in curriculum development. [16][17][18] A Brazilian study comparing motivation of students from a traditional with those studying a reformed curriculum found significant higher motivation levels in the latter, which persisted over the whole study period. 17 The switch away from the traditional curriculum reduced the medical students' levels of anxiety, improved students' metacognitive processing capacity and self-regulated learning skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is something to be improved on in future investigations. On the basis of this study, future work should further explore whether students’ career choice motivations would change as their medical studies progress,45 and if so, to what extent such changes will affect students’ perceptions of medical professionalism.…”
Section: Discussionmentioning
confidence: 99%
“…Even alterations in the traditional curriculum, with a reduction in content and student inclusion since the beginning of the course in primary care settings, together with experience in the community, are associated with increased motivation for learning among the students of the first two years of the course 16 .…”
Section: Discussionmentioning
confidence: 99%